ANALISIS HAMBATAN SANTRI DALAM MEMBACA ARAB GUNDUL DI PESANTREN SALAFI AT-TIBYAN - Alim Budiman; Arin Hamid (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to analyze the challenges faced by students in reading unvowelled Arabic texts (kitab kuning) at the Salafi-based At-Tibyan Islamic boarding school. The research focuses on linguistic, pedagogical, psychological, and environmental factors that contribute to students’ limited literacy in classical Arabic texts. Using a library research method, this study examines scholarly literature, including academic journals, books, and previous research findings. The results indicate that the primary difficulties stem from weak mastery of Arabic grammar (nahwu and sharaf), limited vocabulary, and insufficient systematic reading practice. Pedagogical barriers are linked to traditional teacher-centered methods, while psychological factors such as learning anxiety and low self-confidence exacerbate the issue. Furthermore, the learning environment, which prioritizes spoken Arabic without balancing it with textual literacy training, contributes to a mismatch in students’ language competencies. This research highlights the need for holistic, innovative, and adaptive instructional strategies to improve students’ ability to read classical Arabic texts effectively.